Social and Economic Dependence of Women - Евгения Сергеевна Балабанова (Journal of Economic Sociology, 2010)
Relying on the empirical results the author concludes that the social and economic dependence of females is multivariable. Their dependence in the family is stipulated not by the economic factor but also by non-economic factors such as spouse relations, emotional affection. Under the current culture a woman that has children could change the realms of her dependence but it is much more difficult for her to exit the dependence. The financial dependence of a woman leads to the social dependence during the relation process with her man. Economic dependence from her parents and state has less restriction to her freedom. Economic dependence plays the key role in the gender inequality reproduction: home duties of women limit their possibilities on the labour market and determine the lower wages, that consolidates the established labour division in the family. The issue of the possible overcoming this female dependence remains challenging. The author states that only the changes in the culture, consciousness and mentality could solve the problem.